2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32781
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Differences in Student Motivation for Industry Projects and Non-Industry Projects in Senior Capstone Design

Abstract: I am a graduate student pursuing M.S. in Mechanical Engineering at Florida Institute of Technology with specialization in Structures, Solid Mechanics and Materials. I graduated with B.E. in Mechanical Engineering in India in May 2016. My research is focused on Student's Motivation in Engineering under the advisement of Dr. Beshoy Morkos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…With the adamant of research in reward-based performances, studies highlight two important topics: improving performance [47] and changes in intrinsic motivation [48]. The authors of this study have previously contributed to understanding student motivation in mechanical design courses [49]. The idea of improving motivation and student performance with rewards is controversial [48].…”
Section: -2 / Vol 22 June 2022mentioning
confidence: 99%
“…With the adamant of research in reward-based performances, studies highlight two important topics: improving performance [47] and changes in intrinsic motivation [48]. The authors of this study have previously contributed to understanding student motivation in mechanical design courses [49]. The idea of improving motivation and student performance with rewards is controversial [48].…”
Section: -2 / Vol 22 June 2022mentioning
confidence: 99%
“…Prior research has indicated the importance student motivation has on student performance in a course [31]. Further, we have witnessed how mechanical engineering students in particular possess different types of student motivation [32], particularly toward real-world applications [33]. An assignment as the one proposed in this paper could increase student motivation toward the content, which in turn can improve student performance.…”
Section: Intervention -Manufacturing Assessment Surveymentioning
confidence: 93%
“…al, 2013;Nelson et. al, 2014;Shah et. al, 2019 are a few examples), there have been only a handful of institution level surveys of senior capstone classes and experiences.…”
Section: Literature Reviewmentioning
confidence: 98%